GDF‐15 in solid vs non‐solid treatment‐naïve malignancies. (26th September 2019) - Arfsten, Henrike; Cho, Anna; Freitag, Claudia; Raderer, Markus; Goliasch, Georg; Bartko, Philipp E.; Wurm, Raphael; Strunk, Guido; Gisslinger, Heinz; Marosi, Christine; Kornek, Gabriela; Zielinski, Christoph; et al.
Abstract: Aim: GDF‐15 is an established cardiovascular risk marker but is equally implicated in tumour biology. Elevated levels of GDF‐15 have indeed been observed in distinct tumour entities. This study aimed to explore the relation of GDF‐15 to other cardiac biomarkers and the general association of GDF‐15 on prognosis in an unselected cohort of treatment‐naïve cancer patients. Methods: We prospectively enrolled 555 consecutive patients at time of diagnosis of malignant disease prior receiving anticancer therapy. Plasma GDF‐15 concentrations were determined alongside other cardiac and routine laboratory markers. All‐cause mortality was defined as primary endpoint. Results: GDF‐15 levels were 338 ng/L (IQR:205‐534) for the total cohort, and values were comparable for different tumour entities except breast cancer. Metastatic disease was characterized by higher plasma GDF‐15 [435 ng/L (IQR:279‐614) vs 266 ng/L (IQR:175‐427), P  < .001]. GDF‐15 correlated positively with inflammatory status reflected by CRP, SAA and IL‐6 [ r  = .31, P  < .001, r  = .23, P  < .001 and r  = .14, P  = .002] and cardiac biomarkers as NT‐proBNP, hsTnT, MR‐proADM and CT‐proET‐1 [ r  = .46; r  = .46; r  = .59 and r  = .50; P  < .001 for all]. GDF‐15 was significantly associated with all‐cause mortality after multivariate adjustment [adj.HR for ln(GDF‐15) 1.78, 95%CI:1.47‐2.16, P  < .001]. There was a significant interaction between solid and haematological malignancies with loss of association of GDF‐15 with outcome in myelodysplastic and myeloproliferative disease. Conclusions: Elevated plasma GDF‐15 is associated with progressing disease severity and poor prognosis in solid tumours of treatment‐naïve cancer patients. GDF‐15 increase is accompanied by worsening systemic inflammation and a subclinical functional impairment of different organs including the heart. GDF‐15 represents a promising target for our pathophysiologic understanding in cardio‐oncology linking conditions of both cardiac and neoplastic disease.